Potentials of Egg Shell and Snail Shell Powder in Sorghum Beer Clarification - Jude O. Iwouno; Chigozie E. Ofoedu; Arinze F. Ofoedum (Archives of Current Research International, 2019)
Aim: Turbidity is one of the integral parameters used to ascertain beer quality and clarity. This has been achieved through a combination of filtration processes and utilization of kieselghur as filter aid. Kieselghur on the other hand is expensive and not readily available; therefore there is need to find potential filter aids from locally available materials. The aim of this research is to determine the effectiveness of egg shell powder and snail shell powder in sorghum beer clarification. Study Design: This study was made to fit into using a combination of T-test and one way Analysis of Variance. Place and Duration of Study: The research was carried out at Department of Food Science and Technology Laboratory, Federal University of Technology, Owerri, Nigeria, between May 2018 and November 2018. Methodology: Sorghum grains were malted by adoption of barley malting protocols while snail shells and egg shells obtained from the market were processed into powders. Temperature programmed infusion mashing method was used to produce wort from sorghum malt that was germinated for 2 days and 3 days. The resulting worts were fermented using Saccharomyces carlsbergensis to obtain sorghum beer and the beer was clarified with kieselghur, egg shell powder and snail shell powder. Turbidity and other quality analyses were carried out on the sorghum wort, sorghum beer and clarified sorghum beer. Results: The results showed that beers clarified with Kieselghur had better clarity than egg shell powder and snail shell powder clarified sorghum beers. Egg shell powder showed better clarification potentials than snail shell powder. There is a correlation between total solids and turbidity. Germination period significantly influenced the turbidity of sorghum beer. Conclusion: This study showed that egg shell powder can serve as potential filter aid in beverage clarification.